Achieving SEI preformed graphite in flow cell to mitigate initial lithium loss. (30th August 2022) - Yu, Yikang; Yang, Zhenzhen; Liu, Yuzi; Xie, Jian
Abstract: The irreversible lithium loss due to the formation of solid electrolyte interphase (SEI) in the initial cycle on the graphite anode greatly reduces the overall cell energy density of lithium ion batteries, that is, the lost Li ions from forming SEI lead to the decrease of Li ions for the intercalation. The method of cathode prelithiation has been widely explored to compensate this lithium loss. However, these cathode additives with high lithium contents inevitably lower the loading of the cathode active materials. Here we report a novel approach to solve this challenge, a facile graphite prelithiation method by preforming SEI layers on the surface of graphite powders (Pre-SEI graphite) utilizing a specially designed flow cell. The Li accommodation in the graphite anode can be controlled by the operating time and current density in the flow cell for the electrochemical SEI formation. As a result, we demonstrate a 10% initial Columbic efficiency increase of the LiFePO4 electrode in a full cell configuration using the Pre-SEI graphite, compared with the pristine graphite anode. The electrochemical preformation of SEI on the graphite powders offers a complete solution to offset initial lithium loss without a sacrifice of active cathode material loading. Graphical abstract: Image 1